Adakah Pembaharuan Kewajiban Hak Asasi Manusia pada Badan Usaha Milik Negara? pada sudut pandang Indonesia - Rehulina Rehulina; Katalin Siska Siska; Adrienn Becánics; Orima Davey Orima Davey (Magister of Law, Faculty of Law, University of Mataram, 2026)
State-owned enterprises (SOEs) in Indonesia are at a pivotal intersection of public duty and commercial activity, challenging traditional notions of legal subjectivity under international human rights law. The paper introduces the Indonesian perspective by examining how national business and human rights frameworks apply to SOEs such as PT PLN and PT PERTAMINA, as corporations are required to comply with human rights obligations as part of their international responsibilities. It explores critical research problems, including whether SOEs should bear the same human rights obligations as the state, since it can be argued that SOE constitutes a state itself and how effectively Indonesia's legal instruments address the dual roles of these entities and the challenges posed by multinational corporations with fluid legal identities. The research methodology employs doctrinal legal research utilizing secondary legal data. Preliminary findings indicate that SOEs are state entities with human rights obligations; however, their responsibility is defined as corporate under Pillar Two of the United Nation Guiding Principles on Business and Human Rights (UNGP). Indonesia has effectively integrated the UNGP into its national policies and practices concerning SOEs. The country has updated its National Action Plans on Business and Human Rights and implemented Good Corporate Governance principles to regulate SOE conduct. Prominent companies such as PT PLN and PT Pertamina have adopted measures, including anti-discrimination policies, whistleblowing systems, sustainability reports, and ethical codes of conduct